Development of Human Excretory System Module Based on Problem Based Learning to Improve Student Learning Outcomes in Class XI Science - Sumbayak, Mika Canthika Amelia; Silitonga, Melva; Sitohang, Odelia Nova Maria Br.; Wulandari, Ayu; Sembiring, Gres Anjelia; Rajagukguk, Nia Anggelina; Sitohang, Mohonia Sabarito (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This research aims to develop and test the feasibility and effectiveness of the module of human excretory system based on Problem Based Learning (PBL). The research method use is Research and Development (R&D) with the 4-D model, namely the defining stage, the design stage, the development stage, and the dissemination stage. Validation was conducted by module design experts with an average score of 93.32, material experts 92.32, learning experts 90.86, and one biology teacher of class XI 94.68, all categorized as â€œvery feasible.â€ The module appeal trial shows high results with assessment categories 85.01 - 100 (highly appealing), 70.01 - 85 (appealing), 50.01-70 (less appealing), and 01.00-50 (not appealing). The results of the individual trial were 3 students at 100 (highly appealing), a small group of 10 students at 82.14 (appealing), and a limited group of 20 students at 98.75 (highly appealing). The effectiveness of the module tested through student learning outcomes using independent t test. In the cognitive aspect, the average value of the experimental class reached 96.15 (very good) with t count 2.170 > t table 1.666 and supported by a significant value of 0.033 <0.05. Affective aspects obtained a value of 94.30 (very good) with t count 2.296 > t table 1.666 supported by a significant value of 0.025 < 0.05, and psychomotor aspects reached 97.13 (very good) with t count 7.619 > t table 1.666 supported by a significant value of 0.000 < 0.05. The results of this study indicate that the developed module can be useful as an effective alternative learning media to improve students' learning outcomes.